Pokolenie (bez) rewolucji. Świadectwo nacboli - Kopczacki, Bartłomiej (Rusycystyczne Studia Literaturoznawcze, 2020)
In this article, the author shows that Eduard Limonov’s social and political activity was directed not only at achieving short-term political goals, but also at educating a new generation of Russians. As the head of the National-Bolshevik Party, he was a “godfather” to young people disappointed by the Russian reality of the 1990s and the early years of the presidency of Vladimir Putin. The testimonies in the collections entitled “Лимонка” в тюрьму and “Лимонка” в войну demonstrate that Limonov ultimately achieved his goal of shaping a generation of ideologists ready to sacrifice for their homeland.